Rhythm Control in AF: Have We Reached the Last Frontier? - Gheorghe-Andrei Dan (European Cardiology Review)
AF is a worldwide epidemic, affecting approximately 33 million people, and its rising prevalence is expected to account for increasing clinical and public health costs. AF is associated with an increased risk of MI, heart failure, stroke, dementia, chronic kidney disease and mortality. Preserving sinus rhythm is essential for a better outcome. However, because of the inherent limits of both pharmacological and interventional methods, rhythm strategy management is reserved for symptom and quality-of-life improvement. While ‘classical’ antiarrhythmic drug therapy remains the first-line therapy for rhythm control, its efficacy and safety are limited by empirical use, proarrhythmic risk and organ toxicity. Ablative techniques have had an impressive development, but AF ablation still failed to demonstrate a significant impact on hard endpoints. Understanding of the complex mechanisms of AF will help to develop new vulnerable targets to therapy. Promising molecules are under development, intended to fill the gap between the current pharmacological treatment aimed at maintaining sinus rhythm and the expectations from rhythm strategy.